Resource planner - Rayapati, Navya (Kansas State University, 2016)
When a software development company wants to achieve its goals on time and efficiently use its staff on the projects, it is necessary for the company to have hands on information related to number of employees working on various projects along with their skill set and the number of employees still needed to complete the projects on time. Resource Planner is a convenient tool to handle various projects in a software company efficiently. It is an online tool to manage projects currently running with the company as well as future projects. This tool tracks the employees working for the existing projects and details of new projects like no. of employees required, location, etc., and also estimates revenue which helps higher management to know the status of the various projects and work force. With this tool, HR can estimate the requirement of employees for the new projects and hence can recruit exact number of employees. The project manager can view the details of the employees in the company and the employees in his projects. He can also get the information of how many employees are there in a particular project and their skill set. When he wants employees for a particular project, he can add that information mentioning how many are working on the project and how many employees are totally needed for the project. This information can be had both for online and offline projects. This information is used in generating a special report called GAP summary. This application is developed using Java Spring MVC Framework and MySql database. The main goal of the project is to get familiar with Spring MVC Framework.
Keywords: Spring MVC Framework